Double Inversion Recovery Magnetic Resonance Imaging in Identifying Focal Cortical Dysplasia - Wong-Kisiel, Lily C.; Britton, Jeffrey W.; Witte, Robert J.; Kelly-Williams, Kristen M.; Kotsenas, Amy L.; Krecke, Karl N.; Watson, Robert E.; Patton, Alice; Hanson, Dennis P.; Mandrekar, Jay (Pediatric neurology, 2016)
Focal cortical dysplasia is commonly recognized in pediatric epilepsy surgery. Despite characteristic radiographic features, focal cortical dysplasia can be subtle on magnetic resonance imaging. Double inversion recovery acquisition suppresses the white matter signal, which may enhance visualization of abnormal features at the gray–white matter interface. We assessed the ability of double inversion recovery to distinguish focal cortical dysplasia from periventricular nodular heterotopia and normal brain. Patients with focal cortical dysplasia were identified from our patient database, as was a control group comprising patients with periventricular nodular heterotopia and healthy persons. A senior neuroradiologist reviewed all clinical images and classified them as patients with focal cortical dysplasia (n = 16) or control subjects (periventricular nodular heterotopia, n = 13; normal, n = 20). Four neuroradiologists reviewed the de-identified and randomized double inversion recovery and magnetization prepared rapid acquired gradient echoes (MPRAGE) sequences for each person and scored them as normal, focal cortical dysplasia, or periventricular nodular heterotopia. Among individual reviewers, double inversion recovery showed sensitivity from 50% to 88% and specificity from 67% to 91% in detecting focal cortical dysplasia. The sensitivity was notably higher in reviewers with more clinical experience with the technique. Consensus agreement among the three most experienced reviewers gave a sensitivity of 88% (95% confidence interval [CI], 72% to 97%) and specificity of 88% (95% CI, 62% to 98%) for double inversion recovery and sensitivity of 44% (95% CI, 20% to 70%) and specificity of 100% (95% CI, 89% to 100%) for MPRAGE. Double inversion recovery is sensitive for detection of focal cortical dysplasia with experienced users, particularly when there is consensus agreement. The use of two clinically available magnetic resonance imaging acquisitions—double inversion recovery and another sequence with high specificity such as MPRAGE—would be complementary in the evaluation of lesional epilepsy.